2015
DOI: 10.1124/jpet.115.228825
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Hydrolase Gene Transfer Demonstrates Cardiac Safety and Efficacy against Cocaine-Induced QT Prolongation in Mice

Abstract: Cocaine addiction is associated with devastating medical consequences, including cardiotoxicity and risk-conferring prolongation of the QT interval. Viral gene transfer of cocaine hydrolase engineered from butyrylcholinesterase offers therapeutic promise for treatment-seeking drug users. Although previous preclinical studies have demonstrated benefits of this strategy without signs of toxicity, the specific cardiac safety and efficacy of engineered butyrylcholinesterase viral delivery remains unknown. Here, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…The present study revealed no deficiency in motor or cognition functions in vector-treated mice, and our previous work with the same agent revealed no physiologic side effects other than reduced aggression and longer life in treated mice (51,52). It is worth noting that ghrelin affects not only appetite and weight gain, but also mood, anxiety, fear, and aggression (38,53).…”
Section: Discussionsupporting
confidence: 65%
“…The present study revealed no deficiency in motor or cognition functions in vector-treated mice, and our previous work with the same agent revealed no physiologic side effects other than reduced aggression and longer life in treated mice (51,52). It is worth noting that ghrelin affects not only appetite and weight gain, but also mood, anxiety, fear, and aggression (38,53).…”
Section: Discussionsupporting
confidence: 65%
“…Over the past 10 years, our group performed a series of dose-efficacy and safety experiments in rats and mice for AAV8-hCocH without finding any viral vector-related toxicity. [24][25][26][27] The present study was undertaken to seek further systemic safety data of these high vector doses to define the upper dose limit in the future human trials.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, viral-mediated transfer of BChE did not show signs of motor, cognitive, or cardiovascular toxicity in mice and rats. [172][173][174][175] Despite promising pre-clinical proof of efficacy and safety, it is not yet clear whether gene transfer approaches will be acceptable by the FDA, EMA, or other regulatory agencies. To date, the FDA's Center for Biologics Evaluation and Research (CBER) has not yet approved any human gene therapy product for market.…”
Section: Gene Therapymentioning
confidence: 99%